Three routes for sustainable consumer behaviours - Nascimento, J.; Loureiro, S. (ANZMAC 2022: Reconnect & Reimagine: Conference Proceedings, 2022)
As societies become aware of environmental issues, a large portion of consumers are adopting more sustainable lifestyles and refraining from buying certain products (EIB, 2021), with environmental motives predicted to be the top choice criteria for as much as 55% of consumers in the next five years (betterRetailing.com, 2021). An area of particular dispute in literature is between adopting self-oriented (e.g., related with improving our social/self-identity) or altruistic (e.g., environmental-related) motives for explaining sustainable consumer behaviors (SCBs). In particular, social norms (SN) and environmental concerns (EC) are the two most frequently assessed predictors of SCBs according to our exploratory literature review, yet with contradictory findings. The aim of this study is to examine whether consumers, confronted with choosing between environmentally sustainable and non-sustainable products, show higher consideration for social self-enhancement, or environmental motives, and observe to what extent does that influence differs across green categories. We address the following research questions: RQ1: Which green product categories are spontaneously mentioned by consumers? RQ2: To what extent did social and/or environmental factors influenced their choices? RQ3: What other motivations and barriers may affect SCBs?